2006
DOI: 10.1590/s0103-507x2006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Pacientes clínicos referenciados, mas não internados na Unidade de Terapia Intensiva: prevalência, características clínicas e prognóstico

Abstract: JUSTIFICATIVA E OBJETIVOS: A evolução dos pacientes cuja internação é negada nos centros de terapia intensiva (CTI) é pouco conhecida. Os objetivos deste estudo foram comparar as características dos pacientes internados com aqueles que não foram internados em CTI e identificar os fatores associados com o processo de triagem para a internação. MÉTODO: Foi realizado um estudo do tipo coorte

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
0
6
0
2
Order By: Relevance
“…A research that analyzed factors associated with non-hospitalization at ICUs of referred patients identified that age older than 70 years was one of the reasons for refusal. 21 Thus, the presence of younger patients at the public hospitals found in this study may be related with the lack of ICU beds in comparison with demand, turning age into one of the decisive factors when screening and admitting patients at these critical units.…”
Section: Discussionmentioning
confidence: 78%
“…A research that analyzed factors associated with non-hospitalization at ICUs of referred patients identified that age older than 70 years was one of the reasons for refusal. 21 Thus, the presence of younger patients at the public hospitals found in this study may be related with the lack of ICU beds in comparison with demand, turning age into one of the decisive factors when screening and admitting patients at these critical units.…”
Section: Discussionmentioning
confidence: 78%
“…These patients whose admission was denied presented greater lethality. (19) Coronary failure diagnosis is the most frequent in the studied population. This condition was included in the development of SAPS 3 but not in the other indexes which we have studied in this population.…”
Section: Discussionmentioning
confidence: 93%
“…This study evaluated the relationship between the AS and the ICU length of stay after valve surgery, and our results showed good correlation between the logistic AS and the ICU length of stay. (7,9) The predictive power for LOS was observed to be good when the logistic AS was correlated with > 3 days length of ICU stay, while for the additive model predictive power was indefinite. As far as we could assess, this is the first study designed to evaluate the prediction of ICU length of stay without the EuroSCORE.…”
Section: Discussionmentioning
confidence: 99%